Розроблення каталогу навчальних дисциплін “SCIA: E-Catalog. Outline of academic disciplines” - Канюка, Наталія; Трач, Ольга (Видавництво Львівської політехніки, 2018)
For a clear structuring of educational disciplines in accordance with the course of study and in order to promote the information on the direction of prepa-ration, it is expedient to create a catalog of educa-tional disciplines.
Keywords: навчальна дисципліна; перелік; каталог; навчальна програма; кафедра; заклад вищої освіти